TRPA1 exacerbates selective retinal ganglion cell vulnerability under acute ocular hypertension - Wenhan Lu; Yu Wang; Wei Hu; Xinyi Lin; Xiaoyu Tong; Yi Tian; Yuning Chen; Yicong Wang; Yan Xiao; Hongfang Yang; Yi Feng; Xinghuai Sun (Acta Neuropathologica Communications)
Abstract Acute ocular hypertension (AOH), a major cause of progressive irreversible vision loss, showed significant retinal ganglion cell (RGC) degeneration as well as selective RGC vulnerability upon functional tests, yet the underlyding mechanisms remain incompletely understood. Here, we report the activation of transient receptor potential ankyrin 1 (TRPA1), a mechanosensitive ion channel on RGCs under AOH by RT-qPCR, Western blot, immunofluorescent, flow cytometry and calcium imaging tests. Downstream CaMKII/CREB pathways were evaluated, showing significantly elevated phospho-CaMKII and down-regulated phospho-CREB1 under AOH. Further, by applying a modified whole-brain clearing method, the region-specific RGC axonal damage among lateral geniculate nuclei (LGN) subregions were adopted to detect the involvement of TRPA1 on selective RGC vulnerability. Together with tissue-specific knock-out or channel inhibition test, the exacerbation of TRPA1 on RGC degeneration as well as selective injury tendency under AOH was confirmed. In virtue of our modified whole-brain clearing method, our data confirmed the innovational method to study the mechanisms behind selective vulnerability of neuronal cells, and in the meantime revealed the potential therapeutic opportunity of targeting TRPA1 for patients suffering from AOH attack.